WOVEN FRAMES IN TENSOR PRODUCT OF HILBERT SPACES - S. Afshar Jahanshahi; A. Ahmadi (Journal of Algebraic Systems, 2020)
‎‎The tensor product is the fundemental ingredient for extending one-dimensional techniques of filtering and compression in signal preprocessing to higher dimensions‎. ‎Woven frames play ‎ a crucial role in signal preprocessing and distributed data processing‎. Motivated by these facts, we have investigated the tensor product of woven frames and presented some of their properties. Besides, we have studied some effects of operators on woven frames in the tensor products of Hilbert spaces.